Dystrophin deficiency affects human astrocyte properties and response to damage. Issue 3 (13th November 2021) - Lange, Jenny; Gillham, Olivia; Alkharji, Reem; Eaton, Simon; Ferrari, Giulia; Madej, Monika; Flower, Michael; Tedesco, Francesco Saverio; Muntoni, Francesco; Ferretti, Patrizia
Abstract: In addition to progressive muscular degeneration due to dystrophin mutations, 1/3 of Duchenne muscular dystrophy (DMD) patients present cognitive deficits. However, there is currently an incomplete understanding about the function of the multiple dystrophin isoforms in human brains. Here, we tested the hypothesis that dystrophin deficiency affects glial function in DMD and could therefore contribute to neural impairment. We investigated human dystrophin isoform expression with development and differentiation and response to damage in human astrocytes from control and induced pluripotent stem cells from DMD patients. In control cells, short dystrophin isoforms were up‐regulated with development and their expression levels changed differently upon neuronal and astrocytic differentiation, as well as in 2‐dimensional versus 3‐dimensional astrocyte cultures. All DMD‐astrocytes tested displayed altered morphology, proliferative activity and AQP4 expression. Furthermore, they did not show any morphological change in response to inflammatory stimuli and their number was significantly lower as compared to stimulated healthy astrocytes. Finally, DMD‐astrocytes appeared to be more sensitive than controls to oxidative damage as shown by their increased cell death. Behavioral and metabolic defects in DMD‐astrocytes were consistent with gene pathway dysregulation shared by lines with different mutations as demonstrated by bulk RNA‐seq analysis. Together, our DMD model provides evidence for altered astrocyte function in DMD suggesting that defective astrocyte responses may contribute to neural impairment and might provide additional potential therapeutic targets. Main Points: Dystrophin protein isoforms change with neural differentiation. Dystrophin mutations causing Duchenne muscular dystrophy (DMD) affect astrocytes. DMD astrocytes display an activated phenotype under basal conditions and abnormal response to LPS/IFNγ. DMD astrocytes have increased vulnerability to oxidative damage consistent with metabolic pathway changes.